Harvesting System for Autonomous Robotic in Agriculture: A Review. - Reza Rahmadian; Mahendra Widyartono (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2019)
Technology in the modern day has led to the development of agricultural robots that helps to increase the agriculture productivity. Numerous research has been conducted to help increasing the capability of the robot in assisting agricultural operation, which leads to development of autonomous robot. The development aim is to help reducing agricultures dependency on operators, workers, also reducing the inaccuracy caused by human errors. There are two important development components for autonomous harvesting. The first component is Machine vision for detecting the crops and guiding the robot through the field and the second component actuator to grab or picking the crops or fruits.